Promotion: Safety and Health at Work in the fruit farmers of Cundinamarca - Cárdenas Castellanos, Luis Miguel; Hernández Girón, Sonia Elizabeth; Violet Martelo, Bertha Elisa (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
According to the International Labor Organization (OIT), the agricultural sector employs around 1.300 million workers worldwide. In Colombia, approximately 4 million workers are engaged in agricultural activities, an economic sector that has had the highest occupational accident rates in recent years. During 2020, one of the departments with the highest accident rate was Cundinamarca. In accordance with the above, ASAGRAT identified that farmers present the situations mentioned. Therefore, it is necessary to evaluate the occupational risks of the association in the village of Santa Rosa de Tocaima - Cundinamarca.